The Light of Earth : Reflections on a Life in Space - Worden, Al, 1932-2020; French, Francis (Book collections on Project MUSE., 2021)
"Coauthored with spaceflight historian Francis French, "The Light of Earth" is Al Worden's wide-ranging look at the greatest-ever scientific undertaking, in which he was privileged to be a leading participant"--